My America : recipes from a young Black chef - Onwuachi, Kwame; Stein, Joshua David (Alfred A. Knopf, 2022)
"A cookbook celebrating the food of the African diaspora, from Nigeria and Ethiopia to the Bronx, the Caribbean, and the American South, from the James Beard Award-winning author of Notes from a Young Black Chef"--